Ballistic Resistance of Composite Materials Tested by Taylor Anvil Test - Vilis, Jindrich; Pokorny, Zdenek; Zouhar, Jan; Jopek, Miroslav (Manufacturing Technology Journal, 2022)
This study is focused on testing the ballistic resistance of composite materials to define their limit thicknesses according to the US STANDARD NIJ 0101.06, level III. The materials Twaron CT 747, Twaron CT 747 TH110 and Endumax Shield XF33, which are widely used in the manufacture of the ballistic protection systems, were tested. A method known as the Taylor Anvil Test (TAT) was used to verify their ballistic resistance. The missile 7.62 mm M80 was used to test the ballistic resistance of these materials. Within the experimental part, the deformation processes of composite materials were examined after impact by this missile. The value of the traumatic effect according to the US STANDARD NIJ 0101.06 was also measured. The results of the experiment provide an idea of the ballistic resistance of selected materials. Based on the results, TAT proved to be the perspective measurement method for further development and optimalization of the multilayer composite armor.
Keywords: Taylor Anvil Test; Ballistic resistance; Material penetration; Twaron; Endumax